2013
DOI: 10.1017/s0007114513000251
|View full text |Cite
|
Sign up to set email alerts
|

Dietary supplementation with Bifidobacterium lactis NCC2818 from weaning reduces local immunoglobulin production in lymphoid-associated tissues but increases systemic antibodies in healthy neonates

Abstract: Weaning is associated with a major shift in the microbial community of the intestine, and this instability may make it more acquiescent than the adult microbiota to long-term changes. Modulation achieved through dietary interventions may have potentially beneficial effects on the developing immune system, which is driven primarily by the microbiota. The specific aim of the present study was to determine whether immune development could be modified by dietary supplementation with the human probiotic Bifidobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 58 publications
2
9
0
Order By: Relevance
“…In such trials, although gestational age and weight at birth, attendance at pre-school facilities, the presence of siblings and pet ownership are often taken into account during analyses, sex seldom is. However, we have previously shown that diet also influences the response to probiotics (44) and the studies here further demonstrate that some of the impacts of both prebiotic and probiotics on immune development in young piglets were also sex-specific. The combination of environmental, genetic, and phenotypic influences on the response to functional foods may, in part, begin to explain inconsistencies in the outcomes of many reported studies.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In such trials, although gestational age and weight at birth, attendance at pre-school facilities, the presence of siblings and pet ownership are often taken into account during analyses, sex seldom is. However, we have previously shown that diet also influences the response to probiotics (44) and the studies here further demonstrate that some of the impacts of both prebiotic and probiotics on immune development in young piglets were also sex-specific. The combination of environmental, genetic, and phenotypic influences on the response to functional foods may, in part, begin to explain inconsistencies in the outcomes of many reported studies.…”
Section: Discussionsupporting
confidence: 67%
“…As we have previously reported (44), there was an increase in IgG 1 anti-soya antibody in serum of piglets after weaning at 3 weeks old onto soya-based diets. Statistical analysis using sex, NCC2818 supplementation, litter, and treatment as fixed factors demonstrated that there was no significant effect of ovalbumin injection on the level of anti-soya antibody produced in response to weaning onto soya protein (Figure 8B, p = 0.198): therefore, for display ( Figure 8A), animals in groups A and C (shown in Figure 1) were grouped together as were animals in groups B and D. The level of antibody produced after weaning varied between litters, but was significantly increased by supplementation with NCC2818 (Figure 8, p = 0.0111).…”
Section: Antibody Responses To Novel Protein Fed At Weaning Are Highesupporting
confidence: 72%
See 1 more Smart Citation
“…Lower levels of ileal sIgA were observed in pigs fed diets with EB alone, but not in combination with X, compared to the control. This may be related with the improved gut barrier function in the small intestine, which likely resulted in reduced access of microbiota to ileal lamina propria, and hence reduced stimulation of IgA production ( Lewis et al, 2013 ). In piglets, Xiong et al (2015) reported that supplementing a low dosage of chito-oligosaccharide led to an increase in intestinal mucosal IL-10 and sIgA, suggesting immune activation resulted in modulation of cytokines and antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…This same feeding regimen was maintained through the growing-finishing phase and pig performance and carcass characteristics were not affected by DFM addition ( Apgar et al., 1993 ). More recent studies utilizing lactic-acid producing DFM ( Bifidobacterium lactis NCC2818) supplemented to a weanling pig diet produced an up-regulation of proteins associated with epithelial tight cell junctions and reduced IgA in intestinal mucosal tissues, indicating increased gut barrier function ( Lewis et al., 2013 ). It has also been demonstrated that effects of DFM are most likely diet dependent ( Merrifield et al., 2013 , Bailey, 2016 ).…”
Section: Direct-fed Microbials (Dfm) and Yeastmentioning
confidence: 99%